Analysis of Financial Efficiency of Renewable Energy Projects Through a Value-Based Management Approach - Matofani, Maya; Hartati, Sri; Septyani, Devia (International Journal of Social Science, Education, Communication and Economics, 2025)
This study explores the application of the Value-Based Management (VBM) approach in analyzing the financial efficiency of renewable energy projects. As the global demand for clean and sustainable energy increases, renewable energy projects play a strategic role in the energy transition but are often faced with challenges of large initial investment, technological risks, and regulatory uncertainty. The results show that the application of VBM in evaluating renewable energy projects can improve the quality of investment decision making by considering both financial and non-financial aspects holistically. VBM encourages companies to be more selective and strategic in choosing projects that are not only economically feasible, but also socially and environmentally sustainable. In addition, this approach provides a strong framework for aligning managerial objectives with shareholder interests, improving corporate governance, and strengthening transparency in the process of evaluating and reporting project performance.